Efect of maleated anhydride on mechanical properties of rice husk filler reinforced PLA Matrix Polymer Composite - M. Hamdan, M. H.; Siregar, J. P.; M. Rejab, M. R.; Bachtiar, D.; Jamiluddin, J.; Tezara, C. (Springer, 2019)
Polylactic acid (PLA) formulated from corn starch has a bright potential to replace the non-renewable petroleum-based plastics. The combination of PLA and natural fbre has gained interest due to its unique performance, as reported in many researches and industries. Meanwhile, rice husk produced as the by-product of rice milling can be utilised, unless it is turned completely into waste. Therefore, in the present study, the rice husk powder (RHP) was used as a fller in the PLA, so to determine the infuence of the fller loading on the mechanical properties of the PLA composite. A coupling agent was selected for treatment from two options, i.e., maleic anhydride polypropylene (MAPP) and maleic anhydride polyethylene (MAPE), by applying the agents with various loading contents, such as 2, 4 and 6 wt%. The composite was fabricated by using the hot compression machine. Both the treated and untreated RHP–PLA composites were characterised via the tensile, fexural and impact strength tests. The increase in the RHP loading content led to the decrease in the tensile and fexural strengths. The applications of the coupling agents (MAPE and MAPP) did not improve the tensile and impact strengths, but the fexural strength was enhanced.